Abiotic Stress Tolerance and Invasive Potential of Ornamental Plants in the Mediterranean Area: Implications for Sustainable Landscaping - Diana-Maria Mircea; Monica Boscaiu; Radu E. Sestras; Adriana F. Sestras; Oscar Vicente (Agronomy)
Several ornamental species have demonstrated adaptive features that could increase their resilience to the current climate emergency but could also be linked to invasiveness in non-native environments. The present review examines the responses of ornamental plants’ grown in the Mediterranean region to relevant abiotic stress conditions such as drought, salinity, extreme temperatures, heavy metal toxicity, and atmospheric N deposition, emphasising physiological and biochemical responses that allow them to adapt to unfavourable environments. These response mechanisms, although useful for landscaping under challenging climate change effects, would help non-native ornamental plants outcompete native flora, change ecosystem functioning, and ultimately contribute to a loss in biodiversity. Effective management practices for sustainable landscaping ensure the sensible use of native species and the development of non-invasive cultivars to minimise ecological risks. This review attempts to provide information on the ornamental and environmental functions of plants in landscape architecture through the relationships between aesthetic and ecological values under abiotic stress, including their negative environmental impact due to their invasive potential.